Computer-AIDED design of user interfaces IV : (Kluwer Academic Publishers, 2005)
Computer-Aided Design of User Interfaces IV gathers the latest research of experts, research teams and leading organisations involved in computer-aided design of user interactive applications supported by software, with specific attention for platform-independent user interfaces and context-sensitive or aware applications. This includes: innovative model-based and agent-based approaches, code-generators, model editors, task animators, translators, checkers, advice-giving systems and systems for graphical and multimodal user interfaces